2012
DOI: 10.1158/1078-0432.ccr-12-1215
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of the Genetic Landscape of Pancreatic Cancer and Implications for Identification of Potential Long-term Survivors

Abstract: Purpose Genetic alterations of KRAS, CDKN2A, TP53 and SMAD4 are the most frequent events in pancreatic cancer. We determined the extent to which these four alterations are coexistent in the same carcinoma, and their impact on patient outcome. Experimental Design Pancreatic cancer patients who underwent an autopsy were studied (n=79). Matched primary and metastasis tissues were evaluated for intragenic mutations in KRAS, CDKN2A and TP53 and immunolabeled for CDKN2A, TP53 and SMAD4 protein products. The number… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
201
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 239 publications
(226 citation statements)
references
References 31 publications
22
201
2
1
Order By: Relevance
“…These observations should support a genetic progression model of pancreatic carcinogenesis leading to invasive cancer 5, 6, 7, 8, 9, 10. Recently, the estimated lifetime of clonal evolution during PC development and progression based on a computational model using many autopsy cases has been reported 11, 12. This model suggested an average of 11.7 years from the initiating carcinogenesis until development of the parental clone, an average of 6.8 years to the development of metastatic subclones within the primary PC, and an average of 2.7 years until death of the case (Figure 1).…”
Section: Opportunity To Diagnose ‘Early Pancreatic Cancer’mentioning
confidence: 66%
“…These observations should support a genetic progression model of pancreatic carcinogenesis leading to invasive cancer 5, 6, 7, 8, 9, 10. Recently, the estimated lifetime of clonal evolution during PC development and progression based on a computational model using many autopsy cases has been reported 11, 12. This model suggested an average of 11.7 years from the initiating carcinogenesis until development of the parental clone, an average of 6.8 years to the development of metastatic subclones within the primary PC, and an average of 2.7 years until death of the case (Figure 1).…”
Section: Opportunity To Diagnose ‘Early Pancreatic Cancer’mentioning
confidence: 66%
“…In particular, the genetic landscape of PDAC is notable for four frequently mutated genes, classifiable as "driver" genes, including K-RAS, TP53, CDKN2A/p16INK4a, and SMAD4/DPC4. These four genes are well recognized as contributing to the carcinogenesis and maintenance of PDAC, and the simultaneous determination of their status provides important information regarding disease progression and survival 16 . DNA extracted from frozen samples was successfully amplified in 100% of all the original human tumors and CAM tumors specimens, for each studied exon.…”
Section: Mutation Analysismentioning
confidence: 99%
“…We used 20 ng of genomic DNA, as template in nested PCR reactions to amplify DNA fragments corresponding to exons 1 and 2 of K-RAS, TP53 exons 5-9, CDKN2A/p16INK4a exons 1 and 2, and DPC4/SMAD4 exons 0-11. The PCR protocol and the sets of primers have been described in detail previously 16,48 . PCR products were purified using a presequencing kit (Amersham Biosciences, Roosendaal, The Netherlands) and sequenced with both forward and reverse primers using the BigDyeTM Terminator v3.1 Cycle Sequencing Kit (Applied Biosystems, Foster City, CA), with the ABI PRISMTM 3100 Genetic analyzer (Applied Biosystems).…”
Section: Mutation Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Yachida et al [111] demonstrated that among patients with stage I/II disease who had two driver gene alterations, the median disease-free and median overall survival was longer. Also, these patients were significantly more likely to develop oligometastatic failure.…”
Section: The Role Of Geneticsmentioning
confidence: 99%